Threat : Palestinian political prisoners in Israel - Baker, Abeer; Matar, Anat, 1956- (Pluto Press, 2011)
Palestinian prisoners charged with security-related offences are immediately taken as a threat to Israel's security. They are seen as potential, if not actual, suicide bombers.